2017
DOI: 10.4274/tjo.22800
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Corneal Endothelial Cell Density with Corneal Tomographic Parameters in Eyes with Keratoconus

Abstract: Objectives:To examine changes in corneal endothelial cell density (ECD) in different stages of keratoconus and evaluate its correlation with corneal tomographic parameters.Materials and Methods:Two hundred six patients with keratoconus were enrolled in the study. Corneal topography was performed by Sirius (CSO, Italy), which has a rotating Scheimpflug camera and a Placido disc topographer. Automatic endothelial analysis was done with the non-contact endothelial microscope (20x probe) of Confoscan-4 (NIDEK, Jap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…18 However, Bozkurt et al reported that ECD signi cantly decreased with the progression of KC in their study, which consisted of 391 eyes and a mean patient age of 24.2 ± 7.7 years. 10 Goebels et al observed that ECD decreased and CV increased with the progression of keratoconus in their work containing 712 KC cases. 9 Our study comprised only those patients who had not undergone a surgical procedure previously and had no contact lens use history.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…18 However, Bozkurt et al reported that ECD signi cantly decreased with the progression of KC in their study, which consisted of 391 eyes and a mean patient age of 24.2 ± 7.7 years. 10 Goebels et al observed that ECD decreased and CV increased with the progression of keratoconus in their work containing 712 KC cases. 9 Our study comprised only those patients who had not undergone a surgical procedure previously and had no contact lens use history.…”
Section: Discussionmentioning
confidence: 95%
“…Some publications reported lower endothelial cell density (ECD) compared to healthy eyes, whereas others observed no signi cant change. [9][10][11][12] Similarly, several publications in the literature report a decrease in the hexagonal cell percentage (HCP) and an increase in the coe cient of variation (CV) in KC cases, while some studies report no change. [9][10][11][12] Reasons for the different results may be related to the number of patients included in the studies, the distribution of the age range of the patients, the stages of keratoconus, and the previous treatment approaches.…”
Section: Introductionmentioning
confidence: 99%
“… 33 , 34 Bitirgen et al 35 detected a decrease in basal epithelial cells and anterior stromal keratocyte density in corneas affected by KC, but reported no change in posterior stromal keratocyte density, endothelial cell count, or subbasal corneal nerve morphology. Bozkurt et al 36 used corneal topography and noncontact endothelial microscopic data to investigate changes in endothelial density in different stages of KC and determined that endothelial cell count decreased with KC progression.…”
Section: Rigid Gas-permeable Contact Lenses In Keratoconusmentioning
confidence: 99%
“…It is characterized by changes in the structures of corneal epithelium and stroma and stromal thinning associated (3). In addition, specular microscopy also revealed some differences in terms of cell number and morphology in the endothelium compared to healthy individuals (6)(7)(8). Glasses and contact lenses are used for visual rehabilitation in keratoconus.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies revealed that ultraviolet rays led to endothelial toxicity and the number of endothelial cells decreased in the patients following the Corneal Cross-Linking Treatment for Keratoconus, especially the ones with less than 400 µm of corneal thickness and underwent epithelial debridement (12,13). Evaluation of endothelial cell counts and morphology before treatment can help determine whether cross-linking treatment will cause endothelial damage or not and what crosslinking modality should be pursued for the patient (8,13). A healthy corneal endothelium is crucial for patients receieving cross-linking treatment in keratoconus, as well as for patients undergoing keratoplasty.…”
Section: Introductionmentioning
confidence: 99%